Chicken MBD4 Regulates Immunoglobulin Diversification by Somatic Hypermutation - Costello, Ryan; Cantillo, Jose F.; Kenter, Amy L. (Frontiers in Immunology, 2019)
Immunoglobulin (Ig) diversification occurs via somatic hypermutation (SHM) and class switch recombination (CSR), and is initiated by activation‐induced deaminase (AID), which converts cytosine to uracil. Variable (V) region genes undergo SHM to create amino acid substitutions that produce antibodies with higher affinity for antigen. The conversion of cytosine to uracil in DNA promotes mutagenesis. Two distinct DNA repair mechanisms regulate uracil processing in Ig genes. The first involves base removal by the uracil DNA glycosylase (UNG), and the second detects uracil via the mismatch repair (MMR) complex. Methyl binding domain protein 4 (MBD4) is an uracil glycosylase and an intriguing candidate for involvement in somatic hypermutation because of its interaction with the MMR MutL homologue 1 (MLH1). We found that the DNA uracil glycosylase domain of MBD4 is highly conserved among mammals, birds, shark and insects. Conservation of the human and chicken MBD4 uracil glycosylase domain structure is striking. Here we examined the function of MBD4 in chicken DT40 B cells which undergo constitutive SHM. We constructed structural variants of MBD4 DT40 cells using CRISPR/Cas9 genome editing. Disruption of the MBD4 uracil glycosylase catalytic region perturbed SHM frequency in IgM loss assays. We propose a model to account for MBD4 uracil glycosylase activity in conjunction with MMR in SHM.